LEGONG DANCE CREATION OF ARAS KEMBANG WINDHU: AN EXPLORATION OF THE PHILOSOPHY OF TUKAD BINDU HISTORY - Kadek Diah Pramanasari (Yayasan Sinergi Widya Nusantara, 2023)
Purpose: Legong Kreasi Aras Kembang Windhu is an artwork inspired by the mythology surrounding Tukad Bindu. This stream is considered a symbol of the greatness of the creator, representing tenderness in maintaining the purity, cleanliness, and sustainability of water sources as the breath of life. The purpose of this work is to unite aesthetic creativity and history, making Tukad Bindu a source of deep inspiration that reflects the aesthetic imagination of nature and explores Hindu mythological sources related to the beauty of tourist attractions in Denpasar City. Research methods: The method of creating this dance work adopts the angripta-sesolahan approach by I Ketut Suteja through several stages, which include planning, joint prayer rituals, material selection, formation of improvised motion results, and the first performance for evaluation. Findings: The result of the creation of Legong Kreasi Aras Kembang Windhu is a dance work that describes the philosophy of water mythology and relates it to the natural history of Tukad Bindu. The alignment of the history of white and yellow Julit fish in Tukad Bindu is the basis for the depiction of human life in this performance. Through this performance, it is hoped that people can better understand and appreciate the importance of preserving nature, especially water and river areas, and promote awareness of sustainability and natural beauty in harmony. Implications: Basically, Legong Kreasi Aras Kembang Windhu is not just a work of art for a prestigious art event but also a tribute to cultural heritage and an innovative attempt to introduce it to the public uniquely and interestingly.